A mini review on the Lactic Acidosis in goats and its remedial approaches - Asad Ali Khaskheli; Muhammad Ibrahim Khaskheli; Allah Jurio Khaskheli; Arshad Ali Khaskheli (Aceh Journal of Animal Science, 2020)
The current study was performed in order to investigate the threat of lactic acidosis in goats worldwide and explore the curative strategies. In this regards a detailed review was performed, however obtained facts were found to be much interesting and valuable. It was indicated by researchers that lactic acidosis is the most common problem in goats throughout the worlds. It represents significant economic loss due to direct and indirect effects. It was further stated that goats with lactic acidosis show decreased body temperature up to 98.1±0.89 °F, rumen and intestinal movement 0.23±0.48/m, rumen pH 4.8±0.07, blood pH 7.1±0.08, increased respiration rate 56.14±7.15/m and heart rate, 136.28±4.71/m. Affected goats also show signs of dyspnea, anorexia, inactivity, incoordination and recumbancy. The glucose level remains 190.14±36.49 mg/dl, total bilirubin 0.75±0.04 mg/dl, direct bilirubin 0.27±0.03mg/dl, indirect bilirubin 0.40±0.03 mg/dl, alanine aminotransferase ALT 36.42±3.04 U/l and alkaline phosphatase 420±3.65 U/l. Furthermore, Glucose level, total bilirubin, direct bilirubin, indirect bilirubin, ALT (SGPT) and alkaline phosphatase increase with treatment of Cassia Fistula, serum biochemical changes rapidly return to normal compared to treatment with Sodium bicarbonate or Magnesium hydroxide. The ruminal juices changes are also significantly improved with the treatment. The changes in the ingesta color, odor and consistency and rumen pH return to normal with the use of Cassia Fistula, Sodium bicarbonate and Magnesium hydroxide. In conclusion, Cassia fistula, Sodium bicarbonate and Magnesium hydroxide could be used as valuable strategies against lactic acidosis in goats. These therapies have been proved to be effective for treating the acidosis in goats.